STRATEGI BERCERITA UNTUK MENANAMKAN NILAI MORAL PADA ANAK USIA DINI - Wuri Wuryandani (MAJALAH ILMIAH PEMBELAJARAN, 2006)
of state and nation, if we educate them optimally. Education is an effort to develop potentials of the children since earlier ages. One of the education which must be given is moral values, according to anticipate the spreading of the negative behavior done by children, either it is inconsequential or seriously consequential. Besides, it is suitable to the scope of Early Childhood Education, which includes moral and religious values.The way to implant moral values to Early Childhood can be carried out by means of narrating strategy. It is appropriate to the Kohlberg’s theory of moral development. On the other hand, there are more benefits which are possible to get. In fact, many parents have not a lot of time to narrate their children some stories. Most of them, especially mothers, are professional or career women, etc. Nowadays popularity of verbal narration has been surpassed by luster of electronic media and more attractive toys. It was a challenge to parent and teachers to make their verbal narration more attractive. Thus, the message on moral values can be perceived well by the children.In order to make an attractive narration, parents or teachers have to care many aspects related to technique of narrating, i.e. the types of story, the used method, visual-aid instrument, vocalization, gesture, etc. Those can support success of using of narrating strategy to implant moral values for children.